Microfluidic Investigation of the Ion-Specific Effect on Bubble Coalescence in Salt Solutions - Guo, Han (Langmuir : the ACS journal of surfaces and colloids, 2023)
A microfluidic method was developed to study the ion-specific effect on bubble coalescence in salt solutions. Compared with other reported methods, microfluidics provides a more direct and accurate means of measuring bubble coalescence in salt solutions. We analyzed the coalescence time and approach velocity between bubbles and used simulation to investigate the pressure evolution during the coalescence process. The coalescence time of the three salt solutions decreased initially and then increased as the concentration of the salt solution was increased. The concentration with the shortest coalescence time is considered as the transition concentration (TC) and exhibits ion-specific. At the TC, the change in coalescence time indicates a shift in the effect of salt on bubble coalescence from facilitation to initial inhibition. Meanwhile, it can be seen that the sodium halide solutions significantly inhibit the bubble coalescence and the inhibition capability follows the order NaCl > NaBr > NaI. The results of the approach velocity show that the coalescence time decreases with increasing approach velocity, as well as the approach velocity was strongly influenced by concentration. The approach velocity undergoes a significant change at the TC. Furthermore, simulations of bubble coalescence in the microchannel indicate that the vertical pressure gradient at the center point of the bubble pairs increases as bubbles approach, driving liquid film drainage until bubble coalescence. The pressure at the center of the bubble pair reaches the maximum when the bubbles have first coalesced. It was further revealed that the concentration of the salt solution has a significant impact on the maximum pressure, as evidenced by the observed trend of decreasing pressure values with increasing concentrations